(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: “Immunization hesitancy” was a fairly new concept developed by SAGE to measure the rate of hesitation for people to participate in vaccination. Research objectives: Determining the state of hesitancy to vaccinate against COVID-19 and some related factors of people in Dich Vong ward, Cau Giay district, Hanoi, in 2022. Research methodology: This study was conducted with a cross-sectional method, designed questionnaire, and in-depth interview. Research result: The assessment has found that the percentage of people who have hesitating behavior toward COVID-19 vaccination of research subjects in the Dich Vong ward is higher than its percentage at the national level. The percentage of research subjects who have hesitating behavior toward COVID-19 vaccination among the high-risk group of COVID-19 is 25%, especially in the group living in places with more than 5 cases of COVID-19 was 36,3%. There is a difference in the percentage of hesitating behavior toward COVID-19 among high-risk groups with middle & lowrisk groups. The associated factors with hesitating behavior toward COVID-19 in the Dich Vong ward, Cau Giay district, include occupation, the number of COVID-19 in the residence area and attitude towards the proposal of fee collection of COVID-19 vaccination. Conclusion & recommendation: The research shows that the rate of DD in the study subjects in the Dich Vong ward is higher than the national rate. Therefore, it is necessary to strengthen communication and mobilize people to get vaccinated against COVID-19. At the same time, develop communication programs to improve people’s knowledge and develop training programs for ward health workers and population leaders.